Pembrolizumab-based first-line treatment for PD-L1-positive, recurrent or metastatic head and neck squamous cell carcinoma: a retrospective analysis - Alessio Cirillo; Daniele Marinelli; Umberto Romeo; Daniela Messineo; Francesca De Felice; Marco De Vincentiis; Valentino Valentini; Silvia Mezi; Filippo Valentini; Luca Vivona; Antonella Chiavassa; Bruna Cerbelli; et al. (BMC Cancer, 2024)
Abstract Background The KEYNOTE-048 trial showed that pembrolizumab-based first-line treatment for R/M HNSCC led to improved OS in the PD-L1 CPS ≥ 1 population when compared to the EXTREME regimen. However, the R/M HNSCC real-world population is generally frailer, often presenting with multiple comorbidities, worse performance status and older age than the population included in phase III clinical trials. Methods This is a retrospective, single-centre analysis of patients with R/M HNSCC treated with pembrolizumab-based first-line treatment. Results From February 2021 to March 2023, 92 patients were treated with pembrolizumab-based first-line treatment. Patients treated with pembrolizumab-based chemoimmunotherapy had better ECOG PS and younger age than those treated with pembrolizumab monotherapy. Median PFS and OS were 4 months and 8 months, respectively. PFS was similar among patients treated with pembrolizumab-based chemoimmunotherapy and pembrolizumab monotherapy, while patients treated with pembrolizumab monotherapy had worse OS (log-rank p =.001, HR 2.7). PFS and OS were improved in patients with PD-L1 CPS > = 20 (PFS: log-rank p =.005, HR 0.50; OS: log-rank p =.04, HR 0.57). Patients with higher ECOG PS scores had worse PFS and OS (PFS, log-rank p =.004; OS, log-rank p = 6e-04). In multivariable analysis, ECOG PS2 was associated with worse PFS and OS. Conclusions PFS in our real-world cohort was similar to the KEYNOTE-048 reference while OS was numerically inferior. A deeper understanding of clinical variables that might affect survival outcomes of patients with R/M HNSCC beyond ECOG PS and PD-L1 CPS is urgently needed.